A Dual Role of P53 in Regulating Colistin-Induced Autophagy in PC-12 Cells - Lu, Ziyin; Chen, Chunli; Wu, Zhiyong; Miao, Yusong; Muhammad, Ishfaq; Ding, Liangjun; Tian, Erjie; Hu, Wanjun; Ni, Huilin; Li, Rui; Wang, Bo; Li, Jichang (Frontiers in Pharmacology, 2017)
This study aimed to investigate the mechanism of p53 in regulating colistin-induced autophagy in PC-12 cells. Importantly, cells were treated with 125 μg/ml colistin for 12 and 24 h after transfection with p53 siRNA or recombinant plasmid. The hallmarks of autophagy and apoptosis were examined by real-time PCR and western blot, fluorescence/immunofluorescence microscopy and electron microscopy. The results showed that silencing of p53 leads to down-regulation of Atg5 and beclin1 for 12 h while up-regulation at 24 h and up-regulation of p62 noted. The ratio of LC3-II/I and autophagic vacuoles were significantly increased at 24 h, but autophagy flux was blocked. The cleavage of caspase3 and PARP (poly ADP-ribose polymerase) were enhanced, while PC-12-sip53 cells exposed to 3-MA showed down-regulation of apoptosis. By contrast, the expression of autophagy-related genes and protein reduced in p53 overexpressing cells following a time dependent manner. Meanwhile, there was an increase in the expression of activated caspase3 and PARP, condensed and fragmented nuclei were evident. Conclusively, the data supported that silencing of p53 promotes impaired autophagy, which acts as a pro-apoptotic induction factor in PC-12 cells treated with colistin for 24 h, and overexpression of p53 inhibits autophagy and accelerates apoptosis. Hence, it has been suggested that p53 could not act as a neuro-protective target in colistin-induced neurotoxicity.